2018
DOI: 10.1016/j.pan.2017.11.011
|View full text |Cite
|
Sign up to set email alerts
|

International consensus on definition and criteria of borderline resectable pancreatic ductal adenocarcinoma 2017

Abstract: This statement was developed to promote international consensus on the definition of borderline resectable pancreatic ductal adenocarcinoma (BR-PDAC) which was adopted by the National Comprehensive Cancer Network (NCCN) in 2006, but which has changed yearly and become more complicated. Based on a symposium held during the 20th meeting of the International Association of Pancreatology (IAP) in Sendai, Japan, in 2016, the presenters sought consensus on issues related to BR-PDAC. We defined patients with BR-PDAC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
398
3
32

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 522 publications
(492 citation statements)
references
References 30 publications
1
398
3
32
Order By: Relevance
“…Although there is a report in which authors demonstrated worse survival for types III and IV vascular resections in pancreatic resections, our study did not show the same relationship with major complications, leading us to recommend resections of larger pancreatic lesions involving retroperitoneal vascular structures. The main limiting factor in this study appeared to be the possibility of vascular reconstruction and the possibility to obtain resection with negative margins, expanding the indications for resection of locally advanced borderline tumors . It is worth noting, however, that in our series more than half of the cases had types III and IV reconstructions, which may have led to worse than expected survival rates.…”
Section: Discussionmentioning
confidence: 82%
“…Although there is a report in which authors demonstrated worse survival for types III and IV vascular resections in pancreatic resections, our study did not show the same relationship with major complications, leading us to recommend resections of larger pancreatic lesions involving retroperitoneal vascular structures. The main limiting factor in this study appeared to be the possibility of vascular reconstruction and the possibility to obtain resection with negative margins, expanding the indications for resection of locally advanced borderline tumors . It is worth noting, however, that in our series more than half of the cases had types III and IV reconstructions, which may have led to worse than expected survival rates.…”
Section: Discussionmentioning
confidence: 82%
“…613 Although some patients are treated with an aggressive surgery-first approach and adjuvant systemic therapies, a preoperative chemotherapy and/or chemoradiation approach is becoming more common for all patients with BRPC. 14 The pre-operative treatment approach for the treatment of patients with BRPC has many potential benefits including a higher likelihood of achieving an R0 resection and early treatment of systemic disease for undetected micrometastasis. 1518 Furthermore, it allows evaluation of the aggressiveness of the disease resulting in a better selection of surgical candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients with pancreatic cancer present with borderline resectable tumors. The most recent consensus definition of borderline resectable pancreatic cancer includes anatomical considerations (contact with <180 degrees of the superior mesenteric artery and/or celiac artery, short segment contact with the common hepatic artery, and contact or occlusion with the superior mesenteric vein‐portal vein confluence with adequate vein proximal and distal for reconstruction), high‐risk biologic features, and patient performance status . All of these factors make upfront surgery risky, and studies have shown that these patients benefit from neoadjuvant chemotherapy and radiation .…”
Section: Introductionmentioning
confidence: 99%